Return to the Strange Land Antony Tudor and the Royal Ballet - Parry, Jann (Dance Books Ltd., Alton,Hampshire (UK), 2001)
Antony Tudor at the Royal Opera House. One of the most intriguing ending in ballet utterly redeems Shadowplay from obscurity. PALABRAS CLAVE: Antony Tudor, Lilac Garden, Shadowplay.